Supervision and Fingerprint Attendance as Dominant Factors in Enhancing Work Discipline - Fymelia Nova Arifeny; Sih Darmi Astuti (International Journal of Economics, Management and Accounting, 2024)
This research analyzes the influence of supervision, compensation, and the application of fingerprint attendance on work discipline at PT. Chocomory Cokelat Persada, Semarang Regency, a part of the Cimory Group. Although previous studies have highlighted the importance of these factors, there remains a gap in understanding their complex interactions. This study aims to fill this gap by examining the simultaneous effects of supervision, compensation, and fingerprint attendance on work discipline. Utilizing a quantitative approach, in determining the sample using the purposive sampling method. Data were collected from 125 employees from production operator and warehouse operator through online google form questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The findings reveal that supervision significantly improves work discipline. The implementation of fingerprint attendance systems positively impacts work discipline. Conversely, compensation does not significantly effect on work discipline. These results suggest that effective supervision and advanced attendance systems are crucial for fostering a disciplined workforce, whereas compensation alone may not be as impactful. The study provides valuable insights for resource management practitioners and researchers, offering strategies to enhance work discipline and improve organizational success.